2020
DOI: 10.1007/s10029-020-02336-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the fascial closure rate after open abdomen treatment: Results from the European Hernia Society (EuraHS) Registry

Abstract: Purpose Definitive fascial closure is an essential treatment objective after open abdomen treatment and mitigates morbidity and mortality. There is a paucity of evidence on factors that promote or prevent definitive fascial closure. Methods A multi-center multivariable analysis of data from the Open Abdomen Route of the European Hernia Society included all cases between 1 May 2015 and 31 December 2019. Different treatment elements, i.e. the use of a viscer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
5
0
5
Order By: Relevance
“…If DFC cannot be achieved within 8 days, the current trend advocates the initiation of DT [ 7 60 ]. Numerous reports have demonstrated that NPWT with CFT yields better results than NPWT alone, although most study participants evaluated in these prior studies were non-trauma patients [ 2 61 62 ]. Accordingly, the World Society of Emergency Surgery and the Eastern Association for the Surgery of Trauma (EAST) recommended NPWT with CFT as the primary technique for TAC [ 8 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…If DFC cannot be achieved within 8 days, the current trend advocates the initiation of DT [ 7 60 ]. Numerous reports have demonstrated that NPWT with CFT yields better results than NPWT alone, although most study participants evaluated in these prior studies were non-trauma patients [ 2 61 62 ]. Accordingly, the World Society of Emergency Surgery and the Eastern Association for the Surgery of Trauma (EAST) recommended NPWT with CFT as the primary technique for TAC [ 8 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of negative-pressure wound therapy in open abdomen treatment and the risk of fistula development is debated; however, a shorter duration of open abdomen therapy combined with dynamic closure techniques has been shown to be both safe and effective 3 , 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In that study, a remarkable 10-fold risk reduction in enteroatmospheric fistula development was shown when a VPL was used. Moreover, another recent analysis from the EHS Open Abdomen Registry 12 found the combination of negative-pressure wound therapy, VPL, and dynamic closure techniques to be beneficial in terms of achieving fascial closure and thus reducing complications. This was also addressed in the 2018 EHS clinical guidelines 4 on the management of the abdominal wall in the context of open and burst abdomen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But using vacuum-assisted wound closure and mesh-mediated fascial traction (VAWCM) as a measure to dynamically approximate and close the rectus abdominis fascia with staged surgical procedures and a visceral protective layer to the vacuum dressing to avoid entero-atmospheric fistulas, morbidity of that procedure will be much lower than 20 years ago ( Beltzer et al, 2016 ; Coccolini et al, 2018 ; Schaaf et al, 2020 ; Weigelt and Kingman, 1988 ; Willms et al, 2015 , 2020 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%